Student Engagement and Accuracy in AR-Supported Grammar Learning: An Exploratory Study in an EFL Context - Marcos-Bo, Miguel; Belda-Medina, Jose (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This exploratory study examines the use of augmented reality (AR) to support the learning of English conditional forms, a grammatical area that is traditionally challenging for learners in secondary education. However, evidence of AR’s efficacy for grammar gains in authentic classroom settings is still emerging and often limited by small-scale, descriptive studies. As part of an exploratory intervention, a convenience sample of 92 fourth-year secondary students (aged 14–16) across four classes participated in a one-month period where regular instruction was supplemented with AR activities authored in Onirix and delivered on tablets. A mixed-methods design combined quantitative pre- and post-test results with qualitative data from student questionnaires, classroom observations, and teacher feedback. Descriptive and inferential analyses indicated observable gains in targeted grammatical forms during the instructional unit, with an average accuracy increase of 21 percentage points from preto post-test. Inferential testing showed statistically significant differences for the zero/first and second conditional scores, whereas gains for the third conditional were more limited. Students reported high engagement (82%) and perceived the AR activities as useful for understanding meaning (87%), while teachers observed increased motivation and collaborative learning. Although limited by the convenience sampling and the pre-experimental one-group design, the findings suggest that AR-supported activities may provide a promising complementary approach to grammar instruction in secondary EFL (English as a Foreign Language) classrooms, demonstrating the pedagogical potential of AR authoring tools.